Greece : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This paper provides an assessment of Greece's competitiveness, export performance, and national saving and investment. It examines the Greek tax ratio and structure, and places them in the EU context. It also reviews the design of the various tax categories, and identifies the scope for further simplifying the tax system and broadening the tax base. The paper discusses that it would be desirable to raise the tax ratio through expanding the tax base before considering raising tax rates.